Utilizacao de especies selvagens no melhoramento de mandioca: Passado, presente e futuro - Valle, T.L. (International Center for Tropical Agriculture, 1991)
Cassava is an important crop in the tropics. The Manihot genus had 98 species and no barriers for efficient reproductive isolation have been observed; therefore plant breeders have an immense gene pool to work with. Genes from wild species have already been successfully used to obtain var. resistant to CAMV, but attempts to increase root protein content have not been so successful. The availability of genes of cultivated species and the risks of working with little-known wild species notably reduce the possibility of using their genetic resources immediately. However, in the middle- and long-term, advantage should be taken of this rich and promising source of germplasm. The collection and assessment of wild species is therefore considered prioritary. (AS- CIAT)